2019
DOI: 10.1109/access.2019.2953769
|View full text |Cite
|
Sign up to set email alerts
|

A Passenger-Centric Model for Reducing Missed Connections at Low Cost Airports With Gates Reassignment

Abstract: Low cost carriers usually operate from no-frills budget terminals which are designed for quick aircraft turnaround, faster passenger connections with minimal inter-gate passenger transfer times. Such operations are highly sensitive to factors such as aircraft delays, turnaround time and flight connection time and may lead to missed connections for self-connecting transfer passengers. In this paper, we propose a passenger-centric model to analyze the effect of turnaround times, minimum connection times and stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Conflicts, in their model, arose when safe separation and heading threshold was violated between 2 aircraft, using the same taxiway. Clearly most of these studies, are performed with objectives like reducing delays [20] [21], emissions etc. which do not have safety as their prime concern.…”
Section: Taxiway Incurionsmentioning
confidence: 99%
“…Conflicts, in their model, arose when safe separation and heading threshold was violated between 2 aircraft, using the same taxiway. Clearly most of these studies, are performed with objectives like reducing delays [20] [21], emissions etc. which do not have safety as their prime concern.…”
Section: Taxiway Incurionsmentioning
confidence: 99%
“…Pternea [8] mathematically modeled passenger flow time problems in gate allocation and discussed different allocation methods considering passenger transfers and airport layout to prove the reliability of the mathematical model. Ali [9] established a model centered on passengers to analyze the impact of minimum walking distance and random delays on passenger transfers. The optimal gate was selected through a heuristic search algorithm, and simulation results showed that all flight passengers could avoid missing their connections.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, taxi delays lower airline operational efciency as well. For passengers, delays may cause poor travel experience and missed connections [2], [3]. Increasing carbon emissions from congested airports worldwide have exacerbated environmental concerns too [4].…”
Section: Introductionmentioning
confidence: 99%